SUSTAINABLE SUPPLY CHAIN MANAGEMENT OF MALAYSIAN SMALL BUSINESS: AN ACCOUNTING PERSPECTIVE - Marsidi, Asri (International Journal of Supply Chain Management, 2019)
Abstract- Small businesses are perceived as having essential impact to the economy and society particularly in the developing economies. In Malaysia, 98.5% or 907,065 business establishments are Small Medium Enterprises (SMEs) [1]. Nonetheless, it is not easy for the small businesses to sustain in the ups and downs of the economy as well as the increasing competitions from all types of small business such as micro, small and medium businesses. In fact, half of the start-ups Malaysian SMEs failed to continue their businesses during the first 5 years of operation [2]. The handy ways to enhance the sustainability of small businesses could be through providing some appropriate accounting and finance skills and knowledge to the business owners to assist them in managing all the business resources effectively and efficiently. As such, small businesses owners should be made aware of the importance of having at least the basic financial accounting system. With the existence of financial accounting system in the business, the small businesses have the potential to contribute more positive impact to not only the economy but also to the society both in the present and in the future.